Impact of serum creatinine measurement error on dose adjustment in renal failure - Schneider, Verena Janina; Henschel, Volkmar; Tadjalli Mehr, Keyvan; Mansmann, Ulrich; Haefeli, Walter E. (Clinical pharmacology & therapeutics, 2003)
Background Doses of renally eliminated drugs should be adjusted according to kidney function to prevent adverse drug events and cost. Dose adjustment can be based on serum creatinine level, subsequent creatinine clearance estimation, and dosage calculation with consideration of the renal elimination properties of the respective compound. Objective Our objective was to quantify the impact and relevance of serum creatinine measurementerror on dose adjustment in renal failure. Methods We analyzed 27,914 measurements from external quality assessment surveys of 1878 German laboratories that used a kinetic alkaline picrate (69% of results) or an enzymatic method (25%) for creatinine determination. Linear models were fit for both methods combined and separately. On the basis of 95% confidence intervals (CIs) for creatinine values, 95% CIs for drug dosing were calculated. Results The 95% CI for a measured serum creatinine value was 0.80 · Measured value< Reference method value < 1.28 · Measured value for the kinetic alkaline picrate method and 0.87 · Measured value < Reference method value < 1.21 · Measured value for the enzymatic method. Applied to a data set of 6.5 million simulated patients with all possible combinations of characteristics relevant for drug dosing, the dosing error caused by serum creatinine measurement error did not exceed 25% in patients with creatinine clearance estimates lower than 50 mL/min according to the Cockcroft-Gault equation. For drugs completely eliminated by the kidneys in active form, the dosing error was up to 6-fold smaller than that which would occur if doseswere not adjusted. Conclusion The serum creatinine measurement error of current laboratory methods is small and is comparable to other errors influencing dose adjustment. Clinical Pharmacology & Therapeutics (2003) 74, 458-467; doi: 10.1016/S0009-9236(03)00235-2
Gesehen am 25.05.2021